Promoting research excellence new approaches to funding. (OECD, 2014)
National research systems face an increasingly competitive environment for ideas, talent and funds, and governments have shifted funds from institutional core funding to project funding, often on a competitive basis, or reward success in raising third-party funds in performance-based funding schemes. It is in this context that "research excellence initiatives" (REIs) have emerged. This is an instrument designed to encourage outstanding research by providing large-scale, long-term funding to designated research units. They provide funds for research and research-related measures, such as the improvement or extension of physical infrastructure, the recruitment of outstanding researchers from abroad and researcher training. This report presents new evidence on how governments steer and fund public research in higher education and public research institutions through REIs. The report can help inform discussions on future government policy directions by providing information on how REIs work and on the functioning and characteristics of institutions that host centres of excellence. The findings show some of the benefits to be gained through REIs and note some pitfalls to be avoided.